INVENTORY CONTROL OF RAW MATERIALS FOR GUSSET, FR (SOZAI) PRODUCTS USING THE ECONOMIC ORDER QUANTITY METHOD AT PT XYZ - Astriyani Sandya Paramita; Yunda Shofa Fauziyah; Pasti Immanuel Bangun (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
PT XYZ is a national company that produces metal-based automotive components, and one of the products is Gusset, FR (Sozai). The problem that repeatedly occurs in the company is the unstable purchase and use of raw materials for Gusset, FR (Sozai) products, even at certain times the purchase of raw materials exceeds the needs. Therefore, this study aims to determine the number of raw material orders, the total cost of raw material inventory, safety stock and reorder points, and inventory control of raw materials for Gusset, FR (Sozai) products at PT XYZ. The analysis method uses the Economic Order Quantity method. The results showed that the order quantity of JSH590R T 2.0 raw materials was 211,580 units and JSC590R T 1.4 raw materials was 208,600. The calculation of the total inventory cost of JSH590R T 2.0 raw materials and JSC590R T 1.4 raw materials is IDR 38,229,645 each. The safety stock calculation for JSH590R T 2.0 raw materials totaled 49,597 units and a reorder point value of 128,201 units. As for the JSC590R T 1.4 raw material, the safety stock calculation results in 41,054 units and a reorder point value of 115,543 units. Inventory control of JSH590R T 2.0 raw materials and JSC590R T 1.4 raw materials by applying the EOQ method when compared to the company's process results in 32% savings in inventory costs. Thus, the Economic Order Quantity method is said to be able to help the company control its inventory. Keywords: Raw Material Inventory, Gusset FR (Sozai), Economic Order Quantity